A lysozyme amyloid fiber loaded with monatomic zinc bactericidal material and a preparation method thereof

CN122997147APending Publication Date: 2026-10-30CHANGZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611284765.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-24
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0007]然而,现有锌基杀菌材料的制备过程通常以促进锌离子水解、成核和形成氧化锌或其他锌基颗粒为目的,所得锌组分主要以颗粒或晶体形式存在,锌原子在载体表面的分布不均匀,仍存在团聚倾向、活性组分脱落、有效活性位点暴露程度受限等问题

Benefits of technology

(1)本发明通过对溶菌酶进行酸性加热处理,使溶菌酶分子从天然折叠状态转变为淀粉样蛋白纤维结构,分子构象发生显著改变。在这一过程中,部分原本位于溶菌酶分子内部的含氮官能团和含氧官能团得到有效暴露,从而为锌离子的结合提供了更多可利用的作用位点。相较于未经酸性加热处理的天然溶菌酶,本发明中的溶菌酶淀粉样蛋白纤维对锌离子具有更高的负载能力,有利于在较低锌用量条件下实现足够的活性位点数量。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The present application relates to the technical field of wastewater sterilization treatment, and in particular to a lysozyme amyloid fiber loaded with monatomic zinc sterilization material and a preparation method thereof. The sterilization effect of zinc oxide loaded amyloid fiber sterilization material is difficult to reach more than 98%. In view of the above problems, the present application provides a lysozyme amyloid fiber loaded with monatomic zinc sterilization material. The antibacterial material is formed by loading monatomic zinc on the surface of the lysozyme amyloid fiber. The antibacterial material solves the problems of easy aggregation of zinc active components, low atomic utilization rate, and difficult sterilization effect of more than 98% in the existing zinc-based sterilization material, and has good market application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of wastewater sterilization treatment technology, specifically to a sterilization material containing lysozyme amyloid protein fibers loaded with single-atom zinc and its preparation method. Background Technology

[0002] In water treatment engineering practice, bacteria, fungi, and other pathogenic microorganisms proliferating in water bodies not only lead to water quality deterioration but also easily adhere to and multiply on the inner walls of pipes, membrane components, and the surfaces of water treatment equipment, forming biofilms. Biofilm formation can cause a series of engineering problems, such as pipe blockage, membrane fouling, corrosion of metal materials, and decreased heat transfer efficiency, seriously affecting the stable operation of water treatment systems. Furthermore, the continuous proliferation of pathogenic microorganisms in circulating water systems may pose a potential threat to public health and safety. Therefore, developing functional materials that combine high-efficiency bactericidal capabilities, good stability, and easy separation and recovery is of significant practical importance and engineering application value in the field of water treatment.

[0003] Currently, in engineering practice, methods commonly used to control microorganisms in aquatic bodies include chlorine-based disinfectant application, ozone oxidation, ultraviolet irradiation, and the addition of organic or inorganic bactericides. Chlorine-based disinfection is a mature process with low operating costs, but chlorine-based disinfectants may react with natural organic matter in the water to generate potentially hazardous disinfection byproducts. Ozone and ultraviolet light can rapidly inactivate microorganisms, but they require sophisticated equipment and operating conditions and lack the ability to continuously inhibit microbial growth, making them unsuitable for addressing the long-term problem of microbial regrowth in pipe networks. While some organic bactericides have high bactericidal efficiency, they are usually homogeneously dispersed in water, making them difficult to separate and recover after use. Long-term use may also result in pesticide residues, posing a risk of secondary pollution.

[0004] The antibacterial activity of zinc ions and various zinc-based materials is widely recognized. Zinc-active components can inhibit or kill microorganisms by affecting bacterial cell membrane integrity, interfering with bacterial metabolic processes, and influencing the normal function of intracellular proteins and enzymes. However, when soluble zinc salts are used directly for sterilization, zinc ions easily diffuse and are lost freely in water, making them difficult to recover and reuse after use. When zinc oxide or other zinc-based particles are used as sterilization materials, the particles tend to aggregate in the aqueous environment, forming large aggregates that significantly reduce the effective contact area and the exposure of active sites, thus affecting the sterilization efficiency of zinc.

[0005] Compared to zinc-based particles, atomically dispersed zinc active sites offer higher zinc atom exposure and a more uniform local chemical environment, providing more effective active centers even with lower zinc dosages. This allows for reduced metal usage while maintaining bactericidal efficacy. However, the separated zinc atoms exhibit a high tendency to migrate and aggregate, easily forming nanoparticles or even larger zinc compounds during preparation or use. Therefore, a carrier material with abundant active sites is needed to stably load these atoms, effectively maintaining their atomically dispersed state.

[0006] Lysozyme is a natural protein containing amino, carboxyl, hydroxyl, amide, and other nitrogen- and oxygen-containing functional groups. In its native folded state, some functional groups are located inside the lysozyme molecule, limiting the number of interaction sites that can directly contact metal ions and thus restricting its metal ion loading capacity. Previous studies have shown that heating lysozyme under acidic conditions alters its molecular conformation, further exposing some of the nitrogen- and oxygen-containing functional groups that were originally located inside the molecule, thereby providing more interaction sites for zinc ion binding. Based on this, adding zinc ions to the acidically heated lysozyme solution allows the zinc ions to coordinate with the exposed nitrogen- and oxygen-containing functional groups in the lysozyme or engage in other interfacial interactions. Adjusting the pH of the system with a low concentration of ammonia can relatively gently alter the acid-base environment of the reaction system and regulate the local state of zinc ions, such as their hydrolysis state and coordination form. After adjusting the pH with ammonia, a gentle water bath aging process is beneficial for promoting the interaction between zinc ions and nitrogen- and oxygen-containing functional groups in lysozyme, and for stabilizing the binding structure, thus providing favorable conditions for the formation of highly dispersed zinc active sites.

[0007] However, the preparation process of existing zinc-based bactericidal materials usually aims to promote the hydrolysis, nucleation and formation of zinc ions and zinc oxide or other zinc-based particles. The resulting zinc components mainly exist in the form of particles or crystals. The distribution of zinc atoms on the carrier surface is uneven, and there are still problems such as agglomeration tendency, loss of active components and limited exposure of effective active sites. Summary of the Invention

[0008] A problem with existing technologies is that the bactericidal effect of zinc oxide-supported amyloid cellulose bactericidal materials is difficult to reach above 98%. To address this problem, this invention provides a bactericidal material composed of lysozyme-supported amyloid cellulose loaded with single-atom zinc, the preparation method of which includes the following steps: (1) Dissolve lysozyme completely in ultrapure water to obtain a homogeneous lysozyme solution; (2) The pH of the lysozyme solution was adjusted to 1-3 using hydrochloric acid, and then the solution was heated and stirred at 85-95℃ to form a lysozyme amyloid protein fiber solution; (3) Cool the lysozyme amyloid cellulose solution to room temperature, add an inorganic water-soluble zinc salt aqueous solution to the solution, stir and mix evenly to obtain a zinc-based lysozyme amyloid cellulose solution, adjust the pH of the solution to 7-7.4 with dilute ammonia water to obtain the precursor solution; the dry weight ratio of the lysozyme amyloid cellulose solution to the amount of inorganic water-soluble zinc salt is (0.3-0.5) g: (0.8-1) mmol; (4) Place the precursor solution at 35-55℃ and age it in a water bath for at least 1 hour. After the water bath aging is completed, the solution is centrifuged, washed with water, and freeze-dried to obtain the bactericidal material.

[0009] Preferably, the inorganic water-soluble zinc salt in step (3) includes one or more of zinc chloride, zinc nitrate, zinc acetate, and zinc sulfate.

[0010] Preferably, the concentration of hydrochloric acid in step (2) is 0.5-1.0 mol / L.

[0011] Preferably, the mass concentration of the dilute ammonia water in step (3) is 0.2-0.3%.

[0012] Preferably, the concentration of the inorganic water-soluble zinc salt aqueous solution in step (3) is 0.05-0.5 mol / L.

[0013] Preferably, in step (1), the ratio of lysozyme to ultrapure water is (8-10) g : (450-500) mL.

[0014] Preferably, the freeze-drying temperature in step (4) is -30 to -50°C, and the freeze-drying time is at least 18 hours.

[0015] Preferably, pH=2 in step (2).

[0016] Beneficial effects: (1) This invention transforms lysozyme molecules from their natural folded state into amyloid fibrous structures through acidic heating treatment, resulting in a significant change in molecular conformation. During this process, some nitrogen-containing and oxygen-containing functional groups originally located within the lysozyme molecule are effectively exposed, thus providing more available sites for zinc ion binding. Compared to natural lysozyme without acidic heating treatment, the lysozyme amyloid fibrous structures in this invention have a higher zinc ion loading capacity, which is beneficial for achieving a sufficient number of active sites under conditions of lower zinc dosage.

[0017] (2) This invention utilizes the abundant amino, carboxyl, hydroxyl, and amide functional groups in lysozyme amyloid protein fibers to stably load zinc active sites. These functional groups form a relatively strong bond with zinc ions through coordination or other interfacial interactions, effectively limiting the migration and mutual contact of zinc species during preparation and use, which helps to suppress the aggregation tendency of zinc atoms, thereby achieving a high degree of dispersion of zinc active sites on the carrier surface.

[0018] (3) This invention uses low-concentration ammonia water as a pH adjuster to adjust the pH of the reaction system in the zinc loading stage to a neutral range of 7.0 to 7.4. Low-concentration ammonia water can relatively gently change the acid-base environment of the reaction system, avoiding rapid hydrolysis and precipitation of zinc ions due to local pH changes. This mild pH control method is beneficial to controlling the hydrolysis process and aggregation behavior of zinc species in the aqueous phase, providing a suitable chemical environment for sufficient contact and coordination reaction between zinc ions and functional groups on lysozyme fibers, thereby playing a positive role in improving the dispersion uniformity of zinc active sites in the final product.

[0019] (4) This invention adds a water bath aging step after adjusting the pH with ammonia. Water bath aging at a mild temperature of 35-55°C for at least 1 hour promotes a more complete and stable interaction between zinc ions and the nitrogen- and oxygen-containing functional groups in the lysozyme amyloid fibers. This treatment step helps to consolidate the binding structure between the zinc active sites and the carrier, making the distribution of zinc species on the fiber surface more uniform and stable, thereby improving the loading stability of the zinc active sites.

[0020] (5) The zinc active sites in the bactericidal material obtained in this invention exist in an atomically dispersed state, rather than in the form of zinc oxide particles or other zinc-based crystals. Compared with zinc-based particles, the atomically dispersed zinc active sites have a higher degree of zinc atom exposure, which is beneficial to increasing the effective contact between the zinc active components and bacteria. The antibacterial rate of the material obtained in Example 1 reaches over 98%.

[0021] (6) This invention effectively restricts the migration and aggregation of zinc species by stabilizing the zinc active sites through lysozyme amyloid fibrous loading, thereby improving the structural stability of the zinc active sites in the material. This stability is not only reflected in the preparation process, but also in the use and storage of the material, which is beneficial to extending the service life of the material and maintaining stable bactericidal performance. Attached Figure Description

[0022] Figure 1 : These are transmission electron microscope images of the bactericidal material obtained in Example 1, where (a) is a low-magnification transmission electron microscope image and (b) is a partially magnified transmission electron microscope image.

[0023] Figure 2 The images shown are aberration-corrected annular dark-field scanning transmission electron microscope images of the bactericidal material obtained in Example 1 at different magnifications, where (a) is a medium magnification image and (b) is a high magnification image.

[0024] Figure 3 : ADF diagram and elemental distribution diagram of the bactericidal material obtained in Example 1, wherein (a) is the ADF diagram, (b) is the C elemental distribution diagram, (c) is the N elemental distribution diagram, (d) is the O elemental distribution diagram, and (e) is the Zn elemental distribution diagram.

[0025] Figure 4 X-ray diffraction patterns of the bactericidal materials and pure zinc oxide obtained in Comparative Example 3, Example 1, and Comparative Example 7, respectively.

[0026] Figure 5 : X-ray photoelectron spectrum of the bactericidal material obtained in Example 1, where (a) is the full spectrum and (b) is the high-resolution Zn2p spectrum. Detailed Implementation

[0027] The present invention will be described in detail below with reference to embodiments. However, it should be understood that the following embodiments are merely illustrative examples of implementation of the present invention and are not intended to limit the scope of the present invention.

[0028] Unless otherwise specified, all raw materials used in the following embodiments of the present invention are commercially available.

[0029] Example 1 A bactericidal material containing lysozyme amyloid protein fibers loaded with single-atom zinc is prepared as follows: (1) Weigh 10g of lysozyme and add it to 470mL of ultrapure water. Stir at room temperature until there are no obvious particles to obtain a lysozyme solution. While stirring, add 1mol / L hydrochloric acid to the obtained lysozyme solution to adjust the pH of the solution system to 2. Then place the obtained solution at 90℃ and heat and stir for 8h. After that, cool the solution to room temperature to obtain a lysozyme amyloid protein fibrillary solution. (2) Take 20 mL of the lysozyme amyloid cellulose solution obtained in step (1), add 3 mL of zinc chloride aqueous solution with a molar concentration of 0.3 mol / L, stir and mix evenly to obtain zinc-based lysozyme amyloid cellulose solution; (3) While stirring, add 0.25% ammonia water to the zinc-based lysozyme amyloid cellulose solution obtained in step (2) to adjust the pH of the reaction system to 7.2; (4) The reaction system obtained in step (3) was aged in a water bath at 45°C for 2 hours (the water bath aging allows zinc ions to further combine with the nitrogen- and oxygen-containing functional groups in lysozyme) to obtain a suspension. (5) Centrifuge the suspension obtained in step (4) at 4000 rpm for 10 min, remove the supernatant and collect the solid product. Wash the obtained solid product with deionized water 3 times to remove unbound zinc ions and other soluble impurities. (6) The solid product obtained in step (5) is freeze-dried at -40°C for 24 hours to obtain a lysozyme protein fiber bactericidal material loaded with zinc monoatoms.

[0030] Transmission electron microscope image of the bactericidal material obtained in Example 1 is shown in the attached instruction manual. Figure 1 As shown. By Figure 1 (a) It can be seen that the obtained material exhibits a branched, network-like, and irregular aggregated structure; from Figure 1 (b) It can be seen that no obvious large-sized zinc-based particles or regular zinc-based lattice structures were observed in the local area of ​​the material, indicating that the zinc species did not undergo obvious granular aggregation.

[0031] The aberration-corrected annular dark-field scanning transmission electron microscope image of the bactericidal material obtained in Example 1 is shown in the attached instruction manual. Figure 2 As shown. By Figure 2 As the magnification increases, multiple high-contrast sites that are separated from each other can be observed in the material, and no obvious large-sized zinc-based particles or continuous zinc-based lattice structures were observed. Combined with the detection results of Zn element in the material, this indicates that the zinc species have a high degree of dispersion, and the discrete high-contrast sites can serve as microstructural evidence of atomically dispersed zinc active sites.

[0032] The ADF diagram and elemental distribution diagram of the bactericidal material obtained in Example 1 are shown in the attached instruction manual. Figure 3 As shown. By Figure 3 It can be seen that C, N, O and Zn element signals were detected in the material. The Zn element signal was generally distributed in the material region containing C, N and O, and no obvious large-scale Zn element enrichment region was observed, indicating that Zn element has been successfully introduced into the lysozyme material system and has good spatial dispersion.

[0033] Comparative Example 1 is the same as Example 1, except that in step (1) of Comparative Example 1, hydrochloric acid is used to adjust the pH of the solution system to pH=1.

[0034] Comparative Example 2 is the same as Example 1, except that in step (2) of Comparative Example 2, hydrochloric acid is used to adjust the pH of the solution system to pH=3.

[0035] Comparative Example 3 A lysozyme amyloid protein fiber, prepared by the following method: (1) Weigh 10g of lysozyme and add it to 470mL of ultrapure water. Stir at room temperature until there are no obvious particles to obtain a lysozyme solution. While stirring, add 1mol / L hydrochloric acid dropwise to the obtained lysozyme solution to adjust the pH of the solution system to 2. Then place the obtained solution at 90℃ and heat and stir for 8h. After that, cool the solution to room temperature to obtain a lysozyme amyloid protein fibrillary solution. Centrifuge at 4000rpm for 10min, remove the supernatant and collect the solid product. (2) The solid product obtained in step (1) was freeze-dried at -40°C for 24 hours to obtain lysozyme amyloid protein fibers.

[0036] Comparative Example 4 A bactericidal material, prepared by the following method: (1) Weigh 10g of lysozyme and add it to 470mL of ultrapure water. Stir at room temperature until there are no obvious particles to obtain a lysozyme solution. While stirring, add 1mol / L hydrochloric acid to the obtained lysozyme solution to adjust the pH of the solution system to 2. Then place the obtained solution at 90℃ and heat and stir for 8h. After that, cool the solution to room temperature to obtain a lysozyme amyloid protein fibrillary solution. (2) Take 20 mL of the lysozyme amyloid cellulose solution obtained in step (1), add 3 mL of zinc chloride aqueous solution with a molar concentration of 0.3 mol / L, stir and mix evenly to obtain zinc-based lysozyme amyloid cellulose solution; (3) While stirring, add 0.25% ammonia water to the zinc-based lysozyme amyloid cellulose solution obtained in step (2) to adjust the pH of the reaction system to 7.2; (4) Centrifuge the suspension obtained in step (3) at 4000 rpm for 10 min, remove the supernatant and collect the solid product. Wash the obtained solid product with deionized water 3 times to remove unbound zinc ions and other soluble impurities. (5) The solid product obtained in step (4) is freeze-dried at -40°C for 24 hours to obtain a sterilization material that has not undergone water bath aging.

[0037] Comparative Example 5 A bactericidal material, prepared by the following method: (1) Take 20 mL of ultrapure water, add 3 mL of zinc chloride aqueous solution with a molar concentration of 0.3 mol / L, and stir to mix evenly; (2) While stirring, add 0.25% ammonia water dropwise to the resulting solution to adjust the pH of the reaction system to 7.2; (3) The resulting reaction system was aged in a water bath at 45°C for 2 h; (4) Centrifuge the system aged in water bath at 4000 rpm for 10 min, remove the supernatant, wash the obtained solid with deionized water 3 times, and then freeze dry at -40℃ for 24 h to obtain freeze-dried zinc powder, which is the target bactericidal material.

[0038] The bactericidal material in Comparative Example 6 was formed by simply and mechanically mixing the lysozyme amyloid protein fiber obtained in Comparative Example 3 with the freeze-dried zinc powder obtained in Comparative Example 5 at a ratio of 10g:40mg.

[0039] Comparative Example 7 is the same as Example 1, except that in step (3) of Comparative Example 7, ammonia water is used to adjust the pH of the reaction system to 8.0.

[0040] Comparative Example 8 A zinc-based oxide-supported amyloid protein fiber bactericidal material is prepared as follows: (1) Weigh 10g of lysozyme and add it to 470mL of ultrapure water. Stir at room temperature until there are no obvious particles to obtain a lysozyme solution. While stirring, add 1mol / L hydrochloric acid to the obtained lysozyme solution to adjust the pH of the solution system to 2. Then place the obtained solution at 90℃ and heat and stir for 8h. After that, cool the solution to room temperature to obtain a lysozyme amyloid protein fibrillary solution. (2) Take 20 mL of the lysozyme amyloid cellulose solution obtained in step (1), add 3 mL of zinc chloride aqueous solution with a molar concentration of 0.3 mol / L, stir and mix evenly to obtain zinc-based lysozyme amyloid cellulose solution; (3) While stirring, add 1% sodium hydroxide aqueous solution to the zinc-based lysozyme amyloid cellulose solution obtained in step (2) to adjust the pH of the reaction system to 7.2; (4) The reaction system obtained in step (3) was aged in a water bath at 45°C for 2 hours (the water bath aging allows zinc ions to further combine with the nitrogen- and oxygen-containing functional groups in lysozyme) to obtain a suspension. (5) Centrifuge the suspension obtained in step (4) at 4000 rpm for 10 min, remove the supernatant and collect the solid product. Wash the obtained solid product with deionized water 3 times to remove unbound zinc ions and other soluble impurities. The solid product obtained in step (5) was freeze-dried at -40°C for 24 h to obtain lysozyme-loaded zinc oxide bactericidal material.

[0041] The X-ray diffraction patterns of the target bactericidal materials and pure zinc oxide samples obtained in Examples 1, 3, and 7 are shown in the appendix to the instruction manual. Figure 4 As shown. By Figure 4As can be seen, the bactericidal materials obtained in Comparative Example 3 and Example 1 mainly exhibit broadened diffuse diffraction peaks. The pure zinc oxide sample, however, shows obvious crystalline characteristic diffraction peaks. The bactericidal material obtained in Example 1 did not show any obvious characteristic diffraction peaks corresponding to zinc oxide, indicating that under the process conditions of pH 7.2, zinc species did not form a zinc oxide crystalline phase detectable by X-ray diffraction. In contrast, after raising the pH of the zinc-loading stage system to 8.0 in Comparative Example 7, obvious crystalline zinc-based species characteristic diffraction signals appeared in the obtained bactericidal material. This indicates that higher pH conditions promote the hydrolysis and aggregation of zinc species, and the highly dispersed atomic state of zinc element exhibited in the bactericidal material obtained in Example 1 is not observed.

[0042] The X-ray photoelectron spectrum of the bactericidal material obtained in Example 1 is shown in the attached instruction manual. Figure 5 As shown. By Figure 5 (a) As can be seen, characteristic signals of C, N, O, and Zn elements were detected in the material, indicating that Zn element has been successfully introduced into the material system. Figure 5 (b) It can be seen that the bactericidal material exhibits characteristic peaks of Zn 2p3 / 2 and Zn 2p1 / 2 in the ranges of approximately 1021-1023 eV and 1044-1046 eV, respectively, indicating that the Zn element in the bactericidal material obtained in the examples mainly exists in the positive divalent state.

[0043] Performance testing This invention uses 1 hour as the contact time between the material and the bacterial solution, which is a short-term sterilization test condition. The antibacterial rate obtained under the 1-hour short-term contact condition can reflect the initial sterilization ability of the material.

[0044] The LB broth medium described in this invention is Luria-Bertani medium, a commonly used bacterial culture medium in microbial culture, which can be used for the resuscitation, expansion culture and preparation of bacterial suspension of Escherichia coli. The LB broth medium used in this invention was purchased from Tianjin Zhonglian Chemical Reagent Co., Ltd., and its trade name is LB broth medium.

[0045] Escherichia coli was used as a representative Gram-negative bacterium to test the bactericidal properties of the materials obtained in the examples and comparative examples. E. coli was inoculated into LB broth medium and cultured with shaking at 37°C to obtain bacterial suspensions. The bacterial suspensions were diluted to appropriate concentrations and divided into several groups. 0.006 g of the bactericidal material to be tested was added to each group, serving as the experimental group; the bacterial suspensions without added bactericidal material served as the blank control group. After culturing the experimental and blank control groups under the same temperature and time conditions, the number of colonies was counted using the plate spread method, and the antibacterial rate was calculated using the following formula.

[0046] Antibacterial rate = (number of colonies in blank control group - number of colonies in experimental group) / number of colonies in blank control group × 100%.

[0047] The bactericidal performance test results of the materials obtained in the examples and comparative examples are shown in Table 1.

[0048] Table 1 As shown in Table 1, under the conditions of 0.006 g of material and 1 h of contact with Escherichia coli, the antibacterial rate of the zinc-loaded lysozyme amyloid fiber bactericidal material obtained in Example 1 was as high as 98.73%, which was higher than that of the comparative examples. This indicates that the zinc-loaded lysozyme amyloid fiber bactericidal material obtained in Example 1 has good short-term bactericidal performance.

[0049] The antibacterial rate of the single-atom zinc-loaded lysozyme amyloid cellulose bactericidal material obtained in Example 1 was 15.93 percentage points and 9.56 percentage points higher than that of Comparative Examples 1 and 2, respectively. The main difference between Comparative Examples 1 and 2 and Example 1 was that the pH of the acidic heat treatment stage of lysozyme was 1 and 3, respectively, indicating that the pH of the acidic heat treatment stage affects the structural changes of lysozyme, the exposure state of functional groups, and the subsequent loading effect of zinc active sites. Under the experimental conditions of Example 1 of this invention, the antibacterial material obtained at pH 2 exhibited the best bactericidal performance. Compared with the condition of pH 1, the antibacterial rate of the antibacterial material obtained at pH 3 was higher, but still lower than that obtained at pH 2, indicating that both excessively strong and insufficient acidic conditions are not conducive to obtaining a better zinc-loaded structure and bactericidal performance.

[0050] Comparative Example 3, consisting of zinc-free lysozyme amyloid fibers, showed an antibacterial rate of only 12.74%, 85.99 percentage points lower than Example 1. This indicates that the lysozyme material treated with acidic heat itself only exhibited weak bactericidal activity under the experimental conditions. Example 1 showed a significantly improved antibacterial rate after the introduction of zinc active sites, demonstrating that zinc active sites are the main functional component responsible for the high bactericidal performance of the material of this invention.

[0051] Comparative Example 4, consisting of zinc-loaded lysozyme-amyloid fibers that had not undergone water bath aging, showed an antibacterial rate of 84.71%. This indicates that even without water bath aging, the lysozyme-amyloid fibers could still load a certain amount of zinc species and exhibit some bactericidal ability. However, its antibacterial rate was 14.02 percentage points lower than that of Example 1, suggesting that the water bath aging step promotes the interaction between zinc species and nitrogen- and oxygen-containing functional groups in lysozyme, enhances the loading stability of zinc active sites, and improves the bactericidal performance of the resulting material.

[0052] Comparative Example 5 was freeze-dried zinc powder, with an antibacterial rate of 78.34%, indicating that the zinc-based freeze-dried powder itself has a certain bactericidal effect. However, compared with Example 1, its antibacterial rate was 20.39 percentage points lower, indicating that in the absence of lysozyme carriers, zinc species may aggregate, leading to a decrease in the exposure of effective active sites and the efficiency of contact with bacteria.

[0053] Comparative Example 6, a simple physical mixture of lysozyme amyloid cellulose and lyophilized zinc powder, showed an antibacterial rate of 77.07%, which was not only lower than that of Example 1, but also did not exhibit a bactericidal effect superior to lyophilized zinc powder alone. This result indicates that a simple physical mixture of lysozyme material and zinc-based lyophilized powder cannot form stable, atomically dispersed zinc active sites, and no significant simple synergistic effect was observed between the lysozyme material and the zinc-based powder.

[0054] Compared to Example 1, Comparative Example 7 only increased the pH of the system adjusted with ammonia during the zinc loading stage from 7.2 to 8.0, achieving an antibacterial rate of 86.09%, which is 12.64 percentage points lower than the 98.73% of Example 1. (Refer to the accompanying manual.) Figure 4 As can be seen, no obvious diffraction peaks characteristic of zinc oxide crystalline phase were observed in the material obtained in Example 1. However, when the pH of the system during the zinc loading stage increased to 8.0, obvious diffraction signals characteristic of crystalline zinc-based species appeared in the material. This result indicates that the pH during the zinc loading stage has a significant impact on the dispersion state of zinc species; excessively high pH promotes the hydrolysis and aggregation of zinc species, which is not conducive to the formation and maintenance of atomically highly dispersed zinc active sites, and leads to a decrease in the bactericidal performance of the material.

[0055] In Comparative Example 8, the pH adjuster in the zinc loading stage was replaced with a 1% sodium hydroxide aqueous solution. The resulting antibacterial material was zinc oxide-loaded lysozyme amyloid fibers, with an antibacterial rate of 95.36%, indicating that zinc-based composite materials loaded with zinc oxide also have good bactericidal properties. Under the same material addition mass and 1-hour contact conditions, the antibacterial rate of the lysozyme-loaded single-atom zinc material obtained in Example 1 was 98.73%, which was 3.37 percentage points higher than that of Comparative Example 8.

[0056] In summary, the antibacterial material obtained in Example 1 achieved an antibacterial rate of 98.73% under the same material dosage and 1-hour contact conditions, which is higher than that of the comparative examples. A comparison of Example 1 with Comparative Examples 1 and 2 shows that the pH during the acidic heating treatment stage of lysozyme affects the loading of zinc active sites and the bactericidal performance of the material. A comparison with Comparative Example 3 shows that the introduction of zinc active sites is an important factor in achieving high-efficiency bactericidal performance. A comparison with Comparative Example 4 shows that the water bath aging step is beneficial for improving the loading stability of zinc species. A comparison with Comparative Examples 5 and 6 shows that the technical effect of the material of this invention does not originate from a simple combination of lysozyme material and zinc-based powder. A comparison with Comparative Example 7 further shows that the pH during the zinc loading stage is an important process parameter affecting the dispersion state of zinc species and the bactericidal performance of the material. A comparison with Comparative Example 8 further illustrates that single-atom zinc-loaded lysozyme amyloid fibers have a better antibacterial effect.

[0057] Based on the preferred embodiments of the present invention, and through the above description, those skilled in the art can make various changes and modifications without departing from the technical concept of the invention. The technical scope of this invention is not limited to the contents of the specification, but must be determined according to the scope of the claims.

Claims

1. A bactericidal material containing lysozyme amyloid protein fibers loaded with single-atom zinc, characterized in that, The preparation method includes the following steps: (1) Dissolve lysozyme completely in ultrapure water to obtain a homogeneous lysozyme solution; (2) The pH of the lysozyme solution was adjusted to 1-3 using hydrochloric acid, and then the solution was heated and stirred at 85-95℃ to form a lysozyme amyloid protein fiber solution; (3) Cool the lysozyme amyloid cellulose solution to room temperature, add an inorganic water-soluble zinc salt aqueous solution to the solution, stir and mix evenly to obtain a zinc-based lysozyme amyloid cellulose solution, adjust the pH of the solution to 7-7.4 with dilute ammonia water to obtain the precursor solution; the dry weight ratio of the lysozyme amyloid cellulose solution to the amount of inorganic water-soluble zinc salt is (0.3-0.5) g: (0.8-1) mmol; (4) Place the precursor solution at 35-55℃ and age it in a water bath for at least 1 hour. After the water bath aging is completed, the solution is centrifuged, washed with water, and freeze-dried to obtain the sterilization material.

2. The bactericidal material of lysozyme amyloid protein fibers loaded with single-atom zinc according to claim 1, characterized in that, In step (3), the inorganic water-soluble zinc salt includes one or more of zinc chloride, zinc nitrate, zinc acetate, and zinc sulfate.

3. The bactericidal material of lysozyme amyloid protein fibers loaded with single-atom zinc according to claim 1, characterized in that, In step (2), the concentration of hydrochloric acid is 0.5-1.0 mol / L.

4. The bactericidal material of lysozyme amyloid protein fibers loaded with single-atom zinc according to claim 1, characterized in that, In step (3), the mass concentration of dilute ammonia water is 0.2-0.3%.

5. The bactericidal material of lysozyme amyloid protein fibers loaded with single-atom zinc according to claim 1, characterized in that, In step (3), the concentration of the inorganic water-soluble zinc salt aqueous solution is 0.05-0.5 mol / L.

6. The bactericidal material of lysozyme amyloid protein fibers loaded with single-atom zinc according to claim 1, characterized in that, In step (1), the ratio of lysozyme to ultrapure water is (8-10) g : (450-500) mL.

7. The bactericidal material of lysozyme amyloid protein fibers loaded with single-atom zinc according to claim 1, characterized in that, In step (4), the freeze-drying temperature is -30 to -50°C and the freeze-drying time is at least 18 hours.

8. The bactericidal material of lysozyme amyloid protein fibers loaded with single-atom zinc according to claim 1, characterized in that, In step (2), pH=2.

9. A method for sterilizing water, characterized in that, The bactericidal material described in any one of claims 1-8 is used as a bactericide and added to the water body.